EFFECTIVE CONTROL DIRECT SYNTHESIS METHOD COMPLEX DYNAMIC OBJECTS UNDER CONDITIONS LIMITED INFORMATION - Pilishkin , V. N.; Shahlovich , R. A. (Problems of Informatization and Management, 2021)
The problems of constructing nonlinear systems, despite a large number of works devoted to them, remain relevant for the practice and theory of control systems. Many known approaches do not allow taking into account various restrictions imposed directly on the system, as well as the requirements for the nature of its functioning. An approach is proposed for solving such problems.